Molecular epidemiology of pathogenic Leptospira spp. among large ruminants in the Philippines - VILLANUEVA, Marvin A. (J Vet Med Sci, 2016)
The extent of Leptospira infection in large ruminants resulting to economic problems in livestock industry in a leptospirosis-endemic country like the Philippines has not been extensively explored. Therefore, we determined the prevalence and carrier status of leptospirosis in large ruminants using molecular techniques and assessed the risk factors of acquiring leptospirosis in these animals. Water buffalo and cattle urine samples (n=831) collected from 21 farms during 2013–2015 were subjected to flaB-nested PCR to detect pathogenic Leptospira spp. Leptospiral flaB was detected in both species with a detection rate of 16.1%. Leptospiral DNA was detected only in samples from animals managed in communal farms. Sequence analysis of Leptospira flaB in large ruminants revealed the formation of three major clusters with L. borgpetersenii or L. kirschneri. One farm contained Leptospira flaB sequences from all clusters identified in this study, suggesting this farm was the main source of leptospires for other farms. This study suggested that these large ruminants are infected with various pathogenic Leptospira species causing possible major economic loss in the livestock industry as well as potential Leptospira reservoirs that can transmit infection to humans and other animals in the Philippines.